CFD analysis of slipstreaming and side drafting techniques concerning aerodynamic drag in nascar racing - Gan E.C.J.; Fong M.; Ng Y.L. (Penerbit Akademia Baru, 2023)
NASCAR has given enormous concentration on aerodynamics in racing in which drivers rely solely on aerodynamic techniques in pursuit of podium finishes. Since drag accounts for roughly 90% total resistance at top speed, NASCAR drivers have resorted to such techniques in gaining aerodynamic advantages. Presently, there are little in-depth investigations found on slipstreaming in applications of high-speed NASCAR race cars and even lesser to none on side drafting. The effects of slipstreaming were studied by varying the vehicle spacing and platoon population of platoon members, whereas the effects of side drafting were studied by varying the longitudinal position and lateral separation between trailing and leading vehicles. The results prove that slipstreaming is beneficial to platoon members in significantly reducing aerodynamic drag at short vehicle spacings. However, there exists a drag bubble within specific ranges of vehicle spacing where trailing vehicles experience significant drag increments. Increasing the platoon population is found to decrease the average drag values of platoon members to a certain extent. On the other hand, the side drafting study reveals that the leading car undergoes significant drag increments while the trailing car experiences some drag reduction, thus proving substantial aerodynamic advantages for trailing vehicles in raising their overtaking capabilities. 2020 PENERBIT AKADEMIA BARU-All rights reserved.